Biology and Ecology of Sardines and Anchovies. - Ganias, Konstantinos (Taylor and Francis, 2014)
Apart from being commercially and socially significant, anchovies and sardines populations occupy crucial positions in the oceans' ecosystems. Low in the food chain, clupeoids tend towards abundance, as if their purpose in life was to be eaten and fuel the upper levels of marine trophic chains. The present book covers a broad spectrum of topics on the biology (sytematics, phylogeography, reproduction, feeding) and ecology (habitat characterization, recruitment variability) of anchovies and sardines. It also puts together important information on the state of their fisheries, exploitation an.